EVALUATION OF CASH RECEIPT PROCEDURES AT ADVENTIST EDUCATION FOUNDATION WAROPEN PAPUA - Sarini Freidah; Hendrik Manossoh; Stanley Kho Walandouw (ACCOUNTABILITY, 2023)
Every foundation needs cash that must be managed properly, one way to manage cash well is to establish procedures for cash receipts. The object of this research is the Waropen Advent Education Foundation. The purpose of this research is to evaluate the cash receipt procedure. The analytical method used to discuss the problems in this research is descriptive analysis method, which is a method that describes and describes a data or situation and describes or explains in such a way that a conclusion can be drawn to answer the existing problems. The results of the study show that the implementation of the design procedure for cash receipts for tuition payments, school operational assistance funds and educational operational assistance (BOP) is good, it's just that a flowchart design has not been formed in the accounting information system. Evaluation of cash receipts procedures is generated to help the Waropen Adventist Foundation design flowcharts and improve accounting information systems so that they comply with the basic principles of receipt and availability of accurate and sufficient information as internal controls in accountability reports. Keywords: Procedure, Receipt, Cash,